Contractor’s Perception on Factors Causing Cost Overrun in Construction Works of Pakistan - Memon, Abdul Qadir; Memon, Aftab Hameed; Soomro, Mohsin Ali (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper assessed the occurrence and severity level of various factors causing time and cost overrun in construction projects of Pakistan. Investigation was carried out through questionnaire form prepared based on 55 common factors identified from literature. Survey was done amongst the representatives of the contractors involved in handling construction activities in Pakistan. A total of 46 responses gathered against 100 distributed forms were analysed statistically. The results obtained from the analyses based on Average Index values revealed that delay in obtaining permits from the governmental agencies, financial difficulties are common issue faced in construction works of Pakistan. The study also revealed that high cost of machinery & its maintenance, inadequate planning & scheduling and slow information flow between parties have significant effect on time overrun cost while critical factors affecting cost overrun are high cost of machinery & its maintenance, unsuitable construction methods and lack of experience of contractors in affecting project cost. The findings of this study will be helpful for the practitioner in planning for achieving timely completion of the projects and also within the estimated cost.